Age-Friendly Municipalism Practices in Türkiye: A Review in the Context of the Global Network of Age-Friendly Cities and Communities - Kubilay Çakıcı; Enes Atay (Sosyal Siyaset Konferansları Dergisi)
The population of Türkiye and the world is getting older every day. In recent years, policies have been developed to support healthy and harmonious living in urbanizing and ageing areas. This study focuses on age-friendly practices in Turkish municipalities that are part of the World Health Organization Global Network of Age-Friendly Cities and Communities. The mission of the Network is to ensure the sharing and dissemination of best practices and experiences. In line with this mission, it aims to support cities in becoming age-friendly. Six municipalities from Türkiye, including one metropolitan municipality and five metropolitan district municipalities, are part of the Network. These six municipalities constitute the sample of the study. A qualitative method was used in the study. We accessed activity reports from 2020-2023 and strategic plans for 2020-2024 from the corporate websites of the municipalities. We analyzed examples of age-friendly city practices of the municipalities included in the network using the content analysis method. The study concluded that municipalities have started to prioritize age-friendly practices, especially in recent years, and have diversified their practices in this direction. However, activities related to the sub-themes of the age-friendly city concept primarily focus on social support and health services.